Extracorporeal Photopheresis as a Treatment Option for Immune-Related Adverse Events: Two Case Reports and a Prospective Study - Ruf, Theresa; Rahimi, Farnaz; Anz, David; Tufman, Amanda; Salzer, Suzanna; Zierold, Sarah; Tomsitz, Dirk; French, Lars E.; Heinzerling, Lucie (Journal of Immunotherapy, 2024)
The wide use of immune checkpoint inhibitors has increased the frequency of immune-related adverse events (irAEs). While many are managed with corticosteroids or hormone substitution, up to 14.9% of irAEs are steroid-refractory or steroid-dependent and thus require second-line treatment. These should reduce irAE-related morbidity and mortality and induce a few side effects of their own while maintaining the antitumor response. There is little comparative data on second-line therapies for irAEs. Two cases of irAEs could not be sufficiently managed with corticosteroids and subsequently received treatment with extracorporeal photopheresis (ECP), including one patient with immune-related erosive oral lichen planus and one patient with immune-related colitis. In both cases, the irAE resolved with ECP in combination with immunosuppressive drugs, that is 4 weeks and 10 weeks after the start of ECP, respectively. To investigate this approach, a prospective clinical study that compares ECP and other second-line therapies for the treatment of steroid-refractory and steroid-dependent irAEs with regard to immunophenotype and therapy response has been designed. ECP could be a treatment option for steroid-refractory and steroid-dependent irAEs, given its good safety profile and lack of adverse effects on antitumor response. Comparative prospective studies are needed to generate an evidence base.
CRIS-Team Scopus Importer:2024-06-14
Keywords: extracorporeal photopheresis; immune checkpoint inhibitors; immune-related adverse events; second-line immunosuppressants; steroid-dependent; steroid-refractory